Changes in physical activity and related functional and disability levels in the first six months after stroke: A longitudinal follow-up study - Askim, T; Bernhardt, J; Churilov, L; Fredriksen, K; Indredavik, B (Journal of rehabilitation medicine, 2013)
To investigate how physical activity changes over the first 6 months after stroke, and how activity is related to function. A longitudinal study with an initial assessment within 14 days after stroke (in hospital) and follow-up assessments 1, 3 and 6 months later (in-patient rehabilitation or at home). Patients with acute stroke. An accelerometer with a switch tilt was used to measure activity over a period of 24 h on each occasion. The Barthel Index (BI) and Berg Balance Scale (BBS) were applied as functional measures. A total of 28 out of 44 recruited patients were included in the analysis (15 men (53.6%), mean age 79 years). The median time in the upright position increased from 92 min at baseline to 144 min 6 months later. A generalized least-square regression models showed that time in the upright position increased by 2.0 min for every day from baseline to 1 month later (p = 0.003). A single point increase on the BBS was associated with an extra 4.3 min in the upright position (p < 0.001), while a single point increase on the BI was associated with an extra 2.1 min in the upright position (p < 0.001). Activity levels are very low during the first 6 months after stroke. However, time in the upright position was found to increase as function improved.